2022
DOI: 10.1111/omi.12397
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Leuconostoc mesenteroides MJM60376 as an oral probiotic and its antibiofilm activity

Abstract: Lactic acid bacteria have been widely used as probiotics for improving gut health. However, studies on oral probiotics were very limited. In this study, 67 lactic acid bacteria (LAB) were isolated from fermented food and screened for antagonistic activity against Streptococcus mutans, the causative pathogen of dental caries. Leuconostoc mesenteroides MJM60376 showed the highest antagonistic activity against S. mutans KCTC3065. L. mesenteroides MJM60376 also showed oral probiotic characteristics including weak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Moreover, it is also noteworthy that in the caries-free samples, Leuconostoc significantly reduced when the radiation dose reached 80 Gy in our study. Previous studies have revealed that Leuconostoc mesenteroides shows oral probiotic characteristics and possesses strong antagonistic activity against S. mutans ( 25 ), indicating that heavy ion radiation induced an increase in cariogenic Streptococcus and also reduced their antagonistic bacteria to shift the oral microflora.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is also noteworthy that in the caries-free samples, Leuconostoc significantly reduced when the radiation dose reached 80 Gy in our study. Previous studies have revealed that Leuconostoc mesenteroides shows oral probiotic characteristics and possesses strong antagonistic activity against S. mutans ( 25 ), indicating that heavy ion radiation induced an increase in cariogenic Streptococcus and also reduced their antagonistic bacteria to shift the oral microflora.…”
Section: Discussionmentioning
confidence: 99%